Gesetz befiehlt, die „Botschaft“ erklärt. Arbeitsteilung zwischen zwei Textsorten - Bratschi, Rebekka (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2021)
The law and the reasons for the law are usually kept separate. This article shows this using the examples of the “act of parliament” and the “dispatch”, two types of text from the Swiss legislative process, and illustrates the relationship between these two types of text with examples.